Respuestas

¡La mejor respuesta!
2013-09-08T01:52:46+02:00
 \frac{1}{3} (x-y)=11                              \frac{4x}{9} = \frac{3y}{4}
 \frac{1}{3} ( \frac{27y}{16} -y)=11                           16x=27y
 \frac{1}{3} ( \frac{11y}{16} )=11                                x= \frac{27y}{16}
 \frac{11y}{48} =11                                                x= \frac{27.48}{16}
y=48                                                                    x=81
te agradesco yevo barios dias tratando de hacer este taller gracia